Biometry and Radiography of the Ribs in Tiger (Panthera tigris) - Pandey, Yogita; Taluja, J. S.; Shahi, A.; Vaish, Rakhi; Pandey, A.; Gupta, N. (Indian Journal of Veterinary Anatomy, 2018)
Tiger is an endangered species and trading of bones of wild animals is the big reason for poaching in India. These bones were used for the preparation of different medicines etc. To prevent such actions, anatomical knowledge of bones of tiger is necessary. Hence the present study was under taken. The present investigation was carried out on the ribs of five adult tigers of either sex. The characteristic features of the ribs as well asmeasurement of different parameters were taken, with the help of cm scale and thread. Weight and length of individual rib was taken. There were 13 pairs of ribs among which first nine pairs were sternal remaining four pairs were asternal. Ribs consisted of a shaft and two extremities. Shaft of second, third, fourth was flattened and in the middle, it was somewhat thickened and twisted inward. Ribs were radiolucent in lateral view of radiograph. The shaft was thick and was outlined by a radio opaque border around it.